IMPLEMENTASI PRINSIP AKUNTANSI SYARIAH UNTUK UMKM DI KOTA BATU - Sari, Arista Fauzi Kartika; Putri, Fadillah; Putri , Verla Selvia (RISTANSI: Riset Akuntansi, 2025)
This study aims to examine the implementation of sharia accounting principles and financial reporting practices of Micro, Small, and Medium Enterprises (MSMEs) in Batu City. The method used is descriptive qualitative, which allows researchers to gain an in-depth understanding of the experiences and views of MSME actors. Primary data were obtained through interviews with eight MSME actors and direct documentation of their financial recording processes. The data analysis technique consists of three main stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate that of the eight informants, only two informants did not keep records. The rest did record but only limited to income and expenses, or can be called profit and loss reports. Other informants also recorded cash flow and business debt. The informants have also implemented sharia principles in their businesses, namely honesty, fairness, accountability and freedom from usury.